Bahan Ajar E-Modul Menggunakan Aplikasi Sigil pada Materi Transformasi Geometri - Zuzilawati Zuzilawati; Rindang Kembar Sari; Haida Fitri (Rumah Jurnal IAIN Bukittinggi, 2021)
The purpose of this research is to develop e-module teaching materials using the sigil application. The type of this research is research and development (R&D). The development model used is a combination of 3-D and Luther Sutopo models, namely define, design, develop (concept, desing, collecting, assembly, testing and distribution materials). After the product was produced based on the results of product trials for aspects of validity, material experts and media experts obtained 82% which is very valid. Aspects of practicality for teachers and students with a percentage of 78.34% or practical, and for the effectiveness test the effective criteria are 77% while the test results are 82.56% with very effective criteria. So it can be concluded that the design of e-module teaching materials using the sigil application on the subject of Geometric Transformation for class XI SMA students is valid, practical and effective.Tujuan penelitian ini untuk mengembangkan bahan ajar e-modul menggunakan aplikasi sigil. Adapun jenis penelitian ini adalah penelitian dan pengembangan (Research and Development/ R&D). Model pengembangan yang digunakan adalah mengkombinasikan antara 3-D dan model Luther Sutopo yaitu define, design, develop (concept, desing, material collecting, assembly, testing dan distribution). Setelah produk dihasilkan berdasarkan hasil uji coba produk untuk aspek kevalidan pada ahli materi dan ahli media memperoleh 82% yaitu sangat valid. Aspek kepraktisan bagi guru dan siswa dengan persentase 78,34% atau praktis, dan untuk uji efektifitas memperoleh kriteria efektif sebesar 77% sedangkan dari hasil tes diperoleh 82,56% dengan kriteria sangat efektif. Jadi dapat disimpulkan bahwa rancangan bahan ajar e-modul menggunakan aplikasi sigil pada pokok bahasan Transformasi Geometri untuk anak kelas XI SMA dinyatakan valid, praktis dan efektif .